2019
DOI: 10.1002/erv.2676
|View full text |Cite
|
Sign up to set email alerts
|

Associations between interoceptive sensitivity, intuitive eating, and body mass index in patients with anorexia nervosa and normal‐weight controls

Abstract: Reduced perception of bodily signals and low levels of intuitive eating have been reported in patients with anorexia nervosa (AN) compared with normal‐weight individuals. However, findings have been inconsistent and treatment progress might account for some of these inconsistencies. Thirty‐seven inpatients with AN and 39 normal‐weight controls completed a heartbeat perception task and the Intuitive Eating Scale–2. Patients with AN reported lower intuitive eating than controls, whereas interoceptive sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 21 publications
6
37
1
2
Order By: Relevance
“…Contrary to the hypothesis that people with AN would exhibit lowered cardiac interoceptive accuracy compared to HC, the study found no significant differences between groups in heartbeat tracking performance. This is in line with a number of recent studies, including two that were published after the hypotheses for the current study were generated (12)(13)(14). The findings of the present study, and more recent research, contrast with previous research using the heartbeat tracking task in AN which found lowered accuracy in this population (10,11).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Contrary to the hypothesis that people with AN would exhibit lowered cardiac interoceptive accuracy compared to HC, the study found no significant differences between groups in heartbeat tracking performance. This is in line with a number of recent studies, including two that were published after the hypotheses for the current study were generated (12)(13)(14). The findings of the present study, and more recent research, contrast with previous research using the heartbeat tracking task in AN which found lowered accuracy in this population (10,11).…”
Section: Discussionsupporting
confidence: 90%
“…The findings of this study did not support this hypothesis, with no relationships found. Consequently, it is possible that interoceptive accuracy is not linked to alexithymia and autistic traits in AN, and is rather associated with other drivers, such as treatment duration or BMI (14). However, it should be noted that interoceptive accuracy, autism, and alexithymia have not consistently been linked in previous studies: two recent studies have found no associations between autism and interoceptive accuracy in adults (33,34).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations